A Method to Determine Energy and Power of a Fracture Process in Polycrystals by Means of HVTEM - Pedro Alejandro Tamayo-Meza; Viacheslav Alexandrovich Yermishkin; Juan Manuel Sandoval-Pineda; Luis Armando Flores-Herrera; Ricardo Gustavo Rodríguez-Cañizo (Advances in Materials Science and Engineering)
Main crack propagation process in polycrystalline materials is very complex due to intercrystalline sliding mechanism effects. Multiple factors make it considerably difficult to analyze the state of stresses in the crack tip within the theoretical scope of linear fracture mechanics (LFM). As a basis for the suggested Bilby-Cottrell-Swinden model, we propose a method to determine the state of stresses in the tip of a propagating crack in microspecimens subjected to tension and measured inside a high voltage transmission electron microscope (HVTEM). Based on the electron microscopy observations of a main crack and the formation of microcracks in the plastic zone, the J-integral was determined.